An Integrated Efficacy and Safety Analysis of Single-Dose Secnidazole 2 g in the Treatment of Bacterial Vaginosis - Pentikis, Helen (Reprod Sci, 2020)
Bacterial vaginosis (BV) is the most common gynecologic infection in women aged 14 to 49 years. Currently recommended treatments require extended dosing and are thus associated with poor adherence. A single-dose oral granule formulation of secnidazole 2 g (SOLOSEC™ [secnidazole], Symbiomix Therapeutics, a Lupin company, Baltimore, MD), a 5-nitroimidazole antibiotic with antimicrobial activity, has been approved by the US Food and Drug Administration for the treatment of BV in adult women. As part of the US registration package, two randomized, double-blind, placebo-controlled clinical studies were conducted to confirm the efficacy and safety of a novel single-dose oral formulation of secnidazole 2 g. This is an integrated analysis of efficacy and safety results from these studies, pivotal study 1 and pivotal study 2. By combining the results of the two studies, relevant information is presented especially when considering the effect of secnidazole on patients with recurrent episodes of BV and the difference in effect on patients of black race. Single-dose secnidazole 2 g was statistically superior to placebo on all primary and secondary efficacy outcomes in both trials, including clinical outcome responder rate (P < 0.001), achievement of Nugent scores in the normal range of 0 to 3 (P < 0.001), greater numbers of patients as therapeutic outcome responders at the test of cure/end of study visit on days 21–30 (P < 0.001), and fewer patients requiring additional treatment at the test of cure/end of study visit (P < 0.001), supporting the role for single oral dose secnidazole 2 g granules as treatment for women with BV.